A STUDY OF ENGLISH VOCABULARY USED IN ONLINE LAO FOOD RECIPES - Vongsena, Savith; Dennis, Nutprapha (International Journal of Research -GRANTHAALAYAH, 2016)
The purpose of this study is to analyze English vocabulary usage in online Lao recipes from a cooking website. The aim of this study is to analyze frequency of eight categories of parts of speech; noun, pronoun, adjective, verb, adverb, preposition, conjunction and determiner. This study is a survey research. The data collection is from 21 Lao recipes selected for analysis. The researcher maintained the use of data analysis by apparently using the frequency and percentage of various types of part of speech as a tool to use for teaching English language most effectively. According to the aims consisting of types of parts of speech divided into eight categories from an online Lao food recipe site entitled: “Lao recipe from a cooking website” was used for summa -rizing the usage frequency of parts of speech from 21 Lao recipes. In the final conclusion, that was taken from the result it was found that “Noun” is the highest frequency part of speech that was frequently used in recipe writing with a count of 1390 words that is a frequency percentage of 42.78%. That is twice the usage frequency of verb which is ranked second amongst the eight parts of speech. The analysis accounting of “Verb” found that there was a total verb word count of 594 words or 18.28%. In contrast, “Determiner” is the part of speech that was the least frequently used in selected recipes with the total work count of 46 words that is a frequency of 1.44%.